Epidemiological changes in infectious disease incidence during the war in Ukraine: increase in parasitic and zoonotic threats (Environment & Health, 2026)
As a result of full-scale armed aggression against Ukraine, there has been a significant reformatting of the infectious epidemiological landscape, accompanied by an increase in the prevalence of parasitic and zoonotic infections, especially among vulnerable population groups. The aim of the study was to identify the characteristics of the formation and dynamics of infectious epidemiology in wartime, to outline the key risk factors for the growth of parasitic infestations and zoonoses, and to assess their impact on the public health system. Methods included analysis of current epidemiological, clinical, and parasitological studies conducted in Ukraine and the EU between 2021 and 2025: observations among refugee children, surveys of internally displaced persons, clinical data on military personnel, and meta-analysis of publications in SCOPUS, PubMed, and other peer-reviewed sources. The results showed that the war contributed to an increase in cases of parasitic and zoonotic diseases due to deteriorating sanitary conditions, mass migration, ecosystem disruption, and increased human contact with reservoirs of infection. According to the annual report on the state of public health, in 2022, the incidence of ascariasis was 36.85 per 100,000 population, and in 2023, it increased to 40.56 (+8.94%). The highest incidence was recorded in relatively safe regions, while in combat zones the figures were underestimated due to population migration and limited medical supervision. For military personnel, prolonged exposure to conditions of clean water shortages, lack of sanitation and food safety, as well as stress and weakened immunity, increase the risk of infection. Conclusions. The development of a national strategy for controlling parasitic infestations–with protocols for mass treatment, health education programs, and enhanced veterinary and epidemiological surveillance—is a key condition for restoring epidemic stability in Ukraine in the postwar period.
Keywords: infectious epidemiology; parasitic infections; war in Ukraine; internally displaced persons; zoonoses; Blastocystis spp; echinococcosis; Bartonella quintana